Comparison of learning patterns of human body recognition between five-year-old and eight-year-old students in Kubu Raya Regency, West Kalimantan, Indonesia - R Marlina; D Miranda; H Hamdani; A Maulidi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
This research was intended to measure and compare students’ ability in learning human body recognition. Students who were participants in this study were five year-olds in kindergarten and eight-year-olds in elementary school in Kubu Raya Regency, West Kalimantan, Indonesia. They studied in 19 kindergartens and 5 elementary schools in Kubu Raya Regency. The participant of students in kindergarten was 223 and the students from elementary school was 107 students. Both groups learned the human body during as many as three meetings. Data was collected and measured by questionnaire with 7 statements including 2 statements about what they knew before the lesson, 2 statements about what they did during the lesson, and 3 statements about how they did their homework; alone, with their parents, or their friends. Overall, these results indicate that 72% of students in elementary schools were better prepared for the lesson than students in kindergarten, but 89% of students in kindergarten did their homework alone and 63% of students in elementary school did their homework with their parents and their friends. In Summary, five-year-old students in kindergarten are more autonomous than eight-year-old students in elementary school.